Archaeology after interpretation : returning materials to archaeological theory - Alberti, Benjamin, 1968-; Jones, Andrew, 1967-; Pollard, Joshua (Left Coast Press, Inc., 2013)
"A new generation of archaeologists has thrown down a challenge to post-processual theory, arguing that characterizing material symbols as arbitrary overlooks the material character and significance of artifacts. This volume showcases the significant departure from previous symbolic approaches that is underway in the discipline. It brings together key scholars advancing a variety of cutting edge approaches, each emphasizing an understanding of artifacts and materials not in terms of symbols but relationally, as a set of associations that compose people's understanding of the world. Authors draw on a diversity of intellectual sources and case studies, paving a dynamic road ahead for archaeology as a discipline and theoretical approaches to material culture"--